2016
DOI: 10.1177/1066896916666319
|View full text |Cite
|
Sign up to set email alerts
|

Dentigerous Cyst and Ameloblastoma of the Jaws

Abstract: The entire clinical team must ensure that a histopathological diagnosis of DC is consistent with the clinicoradiological scenario, particularly in younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…Both are characterized by a structure similar to other nonneoplastic cystic lesions and also share clinical and radiological features with many of them. Very often UA and OKC mimic a dentigerous cyst (DC), and consequently, it is necessary to include them in the differential diagnosis [ 6 – 9 ]. To understand the similarities and differences among them that could be useful for diagnosis and therapeutic purposes, it is important to study the cellular and extracellular elements that take part on the physiopathological mechanisms implicated in their origin and growth; therefore, the aim of this study was to evaluate and compare Ki67, CD138, and the molecular RANK, RANKL, and OPG triad expression on the lining epithelium and stroma of UA, OKC, and DC.…”
Section: Introductionmentioning
confidence: 99%
“…Both are characterized by a structure similar to other nonneoplastic cystic lesions and also share clinical and radiological features with many of them. Very often UA and OKC mimic a dentigerous cyst (DC), and consequently, it is necessary to include them in the differential diagnosis [ 6 – 9 ]. To understand the similarities and differences among them that could be useful for diagnosis and therapeutic purposes, it is important to study the cellular and extracellular elements that take part on the physiopathological mechanisms implicated in their origin and growth; therefore, the aim of this study was to evaluate and compare Ki67, CD138, and the molecular RANK, RANKL, and OPG triad expression on the lining epithelium and stroma of UA, OKC, and DC.…”
Section: Introductionmentioning
confidence: 99%
“…Tkaczuk et al from their 15-year-experience with the jaw cysts consider jaw cysts occurring in children to be rarely symptomatic (8). Barrett et al suggested that sometimes ameloblastomas were misdiagnosed as dentigerous cysts (9). Saccucci M. et al in their study report have described conservative treatment for 9-year-old child affected by radicular cyst (6).…”
Section: Discussionmentioning
confidence: 99%
“…12 The region in which both lesions are most common is at the jaw, the diagnosis depends largely on the histopathological evaluation and it is in this part where there can be controversy and confusion, according to Ackermann 13 , Philipsen 14 , Robinson 15 , they mention that histologically the degeneration of solid/multicystic ameloblastomas (SMA) should be considered since it is usually extensive and sometimes gives the appearance of a cyst identical to the Dentigerous Cyst; Likewise, it has been studied that the presence of a unicystic Ameloblastoma (UA) lacks a mural or intraluminal component (mainly the luminal or simple variant) and this variant of Ameloblastoma can also give a misinterpretation and considered a simple cyst. [13][14][15][16] For all the above, a representative case of both pathological entities is presented, treated in the Maxillofacial Surgery service of "La Raza" Medical Center.…”
Section: Introductionmentioning
confidence: 99%